Online Clubbing and Digital Drag: Queer Nightlife in Pandemic Times - Brown, Hannah M. (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
In this profile of Club Quarantine, a nightly online LGBTQ+ dance party, Hannah M. Brown writes of the challenges of creating a virtual safe space and ensuring privacy for participants, but also the potential for online events such as this to generate increased queer visibility and connect clubgoers with others around the globe.